Implementation of a Literacy-Based Project-Based Learning (PjBL) Model in Islamic Education and Character Education to Foster Students' Moderate Attitudes - Ela Komala; Tedi Priatna; Erni Haryanti; Maslani Maslani (CV. AFDIFAL MAJU BERKAH, 2025)
This study examines the issue of low reading interest among students, which can negatively affect their literacy skills and behavior. If left unaddressed, this issue could lead to a generation with poor literacy abilities and a lack of moderate attitudes. The purpose of this research is to analyze the planning, implementation, and evaluation processes, as well as the impact of the Literacy-Based Project-Based Learning (PjBL) model in the subject of Islamic Education (PAI) and Character Education on shaping students' moderate attitudes. The study employs a qualitative approach with a case study method. Data collection techniques include observation, interviews, and documentation. The findings indicate several key points: (1) The planning process of PjBL in Islamic Education begins with setting objectives aligned with local contexts and religious values, analyzing student characteristics, adapting teaching strategies, preparing worksheets, and designing evaluation tools. (2) The implementation of PjBL in three junior high schools in Bandung involves teachers assigning project tasks, planning project steps, scheduling, and providing continuous monitoring and guidance throughout the project. (3) The evaluation of PjBL includes assessing students' ability to manage projects, the relevance of the projects to the local context, and the authenticity of the final products, which reflect the success of the PjBL implementation. (4) The literacy-based PjBL model demonstrates a significant impact on fostering students' moderate attitudes, particularly in terms of tolerance, national commitment, anti-violence, and accommodation of local culture, with varied results across the three schools. This study concludes that the Literacy-Based Project-Based Learning (PjBL) model in Islamic Education (PAI) and Character Education effectively supports the development of moderate attitudes in religious practices among students at SMPN 18 Bandung